2015
DOI: 10.1089/end.2014.0866
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Renal Parenchymal Volume Preservation Between Partial Nephrectomy, Cryoablation, and Radiofrequency Ablation Using 3D Volume Measurements

Abstract: TA is associated with less RPV loss than PN in the management of SRM, but there is no difference between modalities of TA (CA vs RFA) or between approaches to PN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 22 publications
(24 reference statements)
2
30
0
Order By: Relevance
“…Woldu et al [36] in their recently published retrospective analysis concluded that ablative therapy modalities including cryoablation and RFA were associated with less Renal Parenchymal Volume (RPV) loss compared to partial nephrectomy with its three modalities (open, laparoscopic and robot assisted). Also in patients with chronic kidney disease who had cryoablation, their renal function was maintained [37,38].…”
Section: Preservation Of Renal Function After Ablative Treatmentmentioning
confidence: 99%
“…Woldu et al [36] in their recently published retrospective analysis concluded that ablative therapy modalities including cryoablation and RFA were associated with less Renal Parenchymal Volume (RPV) loss compared to partial nephrectomy with its three modalities (open, laparoscopic and robot assisted). Also in patients with chronic kidney disease who had cryoablation, their renal function was maintained [37,38].…”
Section: Preservation Of Renal Function After Ablative Treatmentmentioning
confidence: 99%
“…A retrospective review of patients with SRMs treated by partial nephrectomy, cryoablation, or radiofrequency ablation revealed a comparatively decreased renal parenchymal volume loss with thermal ablation versus extirpation [9]. A corresponding and significant decrease in mean glomerular filtration rate (GFR) was also noted (−8.2 versus −13.7 %, respectively) [9]. Ji et al further found improved GFR for laparoscopic CA compared to partial nephrectomy with 5-year follow-up [44].…”
Section: Renal Function Outcomesmentioning
confidence: 99%
“…Conscious sedation can often be used, decreasing the risk of general anesthesia and hospitalization time [7]. Additionally, ablative techniques can limit normal parenchymal damage and therefore play a vital role in the management of patients at risk for end-stage renal disease, including those with solitary kidneys, bilateral renal tumors, and hereditary syndromes predisposing to multiple renal masses [8,9]. As ablative technologies develop and evolve, their role in RCC management will continue to broaden [10].…”
Section: Applications and Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…There appears to be no detrimental loss of renal function even in patients with a single kidney. A recently published retrospective analysis by Woldu and colleagues concluded that ablative therapy modalities including cryoablation and RFA were associated with less renal parenchymal volume (RPV) loss compared to partial nephrectomy with its three modalities (open, laparoscopic and robot-assisted) [30]. It was also shown that renal function was maintained in patients with chronic kidney disease after they had cryoablation [31,32].…”
Section: Renal Function Preservationmentioning
confidence: 99%